(untitled) (European Bison Conservation Newsletter, 2015)
Differences in SNP-substitutions of the major histocompatibility complex (MHC) DRB3 and DQB genes involved in the immune response were shown in the genetic structure of the Belarusian and Polish populations of European bison. Unique and rare alleles, which are valuable for the population, and will contribute to an increase in genetic diversity and the viability of the species, were identified.